Harnessing the power of traceable system C-GAP: homologous-targeting to fire up T-cell immune responses with low-dose irradiation - Weijie Zhuang; Kuangwu Pan; Jie Wu; Leyi Liu; Shiyu Lv; Jiajun Hu; Fangyang Shi; Wei Zhao; Dongsheng Yu (Journal of Nanobiotechnology)
Abstract While radiotherapy-induced immunogenic cell death (ICD) holds potential for enhancing cancer immunotherapy, the conventional high-dose irradiation often leads to an immunosuppressive microenvironment and systemic toxicity. Therefore, a biomimetic nanoplatform cell membrane coated-nitrogen-doped graphene quantum dots combined with Au nanoparticles (C-GAP) was developed in this study. Firstly, homologous and traceable targeting features of C-GAP enables tumor-selective accumulation, providing reference for the selection of the timing of radiotherapy. Secondly, radiosensitization by C-GAP with Low-dose irradiation (LDI) amplifies reactive oxygen species (ROS) generation to trigger potent ICD. Thirdly, remarkable immune remodeling induced by C-GAP enhances CD8+ T cell infiltration and effector function. Single-cell RNA sequencing revealed that C-GAP-LDI combination upregulates TNF and CCL signaling pathway expression in tumor-infiltrating CD8+ T cells which potentiates tumor eradication. Our findings present a novel approach for safe and effective radioimmunotherapy, where C-GAP sensitized LDI achieves therapeutic enhancement through precise ICD induction and systemic immune activation. Graphical Abstract